Steam reforming of acetic acid over NiKOH/Al2O3 catalyst with low nickel loading: The remarkable promotional effects of KOH on activity - Zhang, Z.; Hu, X.; Gao, G.; Wei, T.; Dong, Dehua; Wang, Y.; Hu, S.; Xiang, J.; Liu, Q.; Geng, D. (Elsevier Ltd, 2019)
In this paper, the effects of strong base (KOH) addition on the catalytic performances of Ni/Al2O3 catalysts in acetic acid steam reforming for hydrogen generation was investigated. The addition of KOH drastically changed the physiochemical property and catalytic performances of the nickel–based catalysts. KOH reacted with γ–Al2O3 during calcination, forming ɑ–Al2O3 with Al(OH)3 as a reaction intermediate, which led to reconstruction of the porous structure, merge of small pores, decreased specific area and sintering of nickel. Most importantly, the catalytic activity of nickel–based catalysts were significantly enhanced by the addition KOH, especially the ones with low nickel loading. There are almost no active of 1 wt% Ni/Al2O3 catalyst for steam reforming of acetic acid, while, with adding 5 wt % KOH, activity of the catalyst matched that of 20 wt% Ni/Al2O3. In–situ DRIFTS study showed the involvement of the reactive intermediates including CH3, CH2, CO, COO, COC, CC and absorbed CO2 in acetic acid steam reforming. The Ni/Al2O3 catalyst with low nickel loading had insufficient metallic nickel to gasify these reactive intermediates. The presence KOH effectively aided gasification of the reactive intermediates, and thus significantly promoted the catalytic activity. In addition, the KOH with varied loading significantly affect formation of catalytic coke and polymeric coke formed during the reforming reaction.